Surface modification imparts selectivity, facilitating redox catalytic studies: quinone mediated oxygen reduction. - Mason, J; Batchelor-McAuley, C; Compton, R (2013)
Modifying a gold electrode surface with hydroxy-alkyl-thiols significantly reduces the observed rate of electron transfer. This designed and controlled decrease in electron transfer rate readily allows reversible and irreversible electrode processes to be more clearly delineated. Separation of such voltammetric responses can facilitate the direct study of redox catalytic processes, which would, under other experimental conditions be obscured. The reduction of oxygen by anthraquinone hydroxy derivatives are used as a paradigmatic example, demonstrating the importance of the hydroxyl groups in the reduction process. Specifically, the reduced form of 1,8-dihydroxy-anthraquinone is shown to be significantly more reactive towards oxygen reduction than the 1,4-dihydroxyl analogue.